2018
DOI: 10.1038/s41598-018-22843-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of SK channels, L-type Ca2+ channels, and ryanodine receptors in cardiomyocytes

Abstract: Small-conductance Ca2+-activated K+ (SK) channels regulate the excitability of cardiomyocytes by integrating intracellular Ca2+ and membrane potentials on a beat-to-beat basis. The inextricable interplay between activation of SK channels and Ca2+ dynamics suggests the pathology of one begets another. Yet, the exact mechanistic underpinning for the activation of cardiac SK channels remains unaddressed. Here, we investigated the intracellular Ca2+ microdomains necessary for SK channel activation. SK currents cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Since I KAS is very sensitive to local Ca 2+ between the SK channel and LTCC/RyR (Zhang et al . ), it is possible that I KAS recorded at a fixed global Ca 2+ concentration was not high enough to differentially activate I KAS between sexes. Further studies with dynamical Ca 2+ fluctuations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Since I KAS is very sensitive to local Ca 2+ between the SK channel and LTCC/RyR (Zhang et al . ), it is possible that I KAS recorded at a fixed global Ca 2+ concentration was not high enough to differentially activate I KAS between sexes. Further studies with dynamical Ca 2+ fluctuations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This value quantified by the Hanle model can be compared with independently calculated from the spin diffusion model as already discussed above, i.e. = ( ) 2 / where D is the Einstein diffusion coefficient (its value equal to 0.4−0.56 cm 2 /s was taken from Ref [40]…”
mentioning
confidence: 99%
“…Moreover, the expression of L-type Ca 21 channels plays a significant role in functions of SK2 channels in atrial myocytes. Zhang et al [25] observed the close distribution of SK2, Ca v 1.2 Ca 21 channels and ryanodine receptor type 2 in cardiomyocytes, indicating a spatial relationship between these channels. Three (3) molecules were localised within hundreds of nanometers.…”
Section: Structure and Physiology Of Sk Channelsmentioning
confidence: 98%